The Unmet Need of Rohingya Refugee Children in Bangladesh: : A Sociological Analysis - Zinia, Josinta - (International Journal of Scientific Research and Management (IJSRM), 2018)
Rohingyas are a small Muslim ethnic group of Myanmar those who are not recognized as citizens or one of the 135 recognized ethnic groups in the country. They are the people without any identity, without any home. The aim of the present study is to evaluate the vulnerability of Rohingya refugee children and the military violence of Myanmar against Rohingya people that leads to the complete violation of global human right adopted by United Nations. The study was carried out by descriptive qualitative research techniques. To conduct the study, several Rohingya refugee camps were visited and different literature regarding Rohingya issues were reviewed. The result revealed that the ongoing genocide in Rakhaine state by  Myanmar military force on helpless Rohingya people is a complete violation of human rights. Therefore, it can be concluded  that the crisis make the Rohingya children homeless and lead them to an uncertain future.